The Rare Fern Asplenium grevillei Wall. Ex Hook. Et Grev. (aspleniaceae)-a New Find for Peninsular India - Nair, N. C.; Ghosh, S. R. (Indian Forester, 1978)
Asplenium grevillei is a very rare fern which has not been collected for the last eight decades. It is now recorded for the first time from Keral. Phytogeographical aspect of the present find is discussed. The taxon is considered as endangered and needs conservation.